Health-related quality of life in adolescents with inflammatory bowel disease depends on disease activity and psychiatric comorbidity - Engelmann, Guido; Erhard, D.; Petersen, M.; Parzer, Peter; Schlarb, A. A.; Resch, Franz; Brunner, Romuald; Hoffmann, Georg F.; Lenhartz, H.; Richterich, A. (Child psychiatry & human development, 2015)
Adolescent patients with inflammatory bowel disease (IBD) show an increased risk for behavioral and emotional dysfunction. Health-related quality of life (HRQoL) is influenced by medical illnesses, as well as by psychiatric disorders, but for adolescents with IBD, the extent to which HRQoL is influenced by these two factors is unclear. For 47 adolescent IBD patients, we analyzed disease activity, HRQoL and whether or not a psychiatric disorder was present. Disease activity was estimated using pediatric Ulcerative Colitis Activity Index and pediatric Crohn’s Disease Activity Index. The IMPACT-III and the EQ-5D were used to measure HRQoL and QoL, respectively. In addition, patient and parent diagnostic interviews were performed. 55.3 % patients fulfilled DSM-IV criteria for one or more psychiatric disorders. In all patients, psychiatric comorbidity together with disease activity contributed to a reduction in quality of life. Adolescents with IBD are at a high risk for clinically relevant emotional or behavioral problems resulting in significantly lower HRQoL. We conclude that accessible, optimally structured psychotherapeutic and/or psychiatric help is needed in adolescent patients with IBD.